PENGARUH PENYULUHAN TERHADAP PENGETAHUAN, SIKAP DAN TINDAKAN PETANI JERUK DI DESA KUOK PULAU JAMBU TERKAIT PENGGUNAAN ALAT PELINDUNG DIRI (APD) DARI BAHAYA PESTISIDA - Syafriani Syafriani; Eka Saputri (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2019)
Agricultural counseling is to encourage farmers to change their way of thinking, ways of working and old ways of life with new ways that are more in line with the development of more advanced agricultural technology (Mardikanto, 2013). The purpose of this study was to analyze the effect of counseling on improving the knowledge, attitudes and actions of citrus farmers in Kuok Village, Jambu Island, regarding the use of PPE when applying pesticides. The design of this study was quasi-experimental (quasi-experimental) using one group pretest and posttest design. This research was conducted in July 2019 in Kuok Village, Jambu Island. The population in this study were orange farmers, amounting to 45 people. The sampling technique used is total sampling so the sample size is 45 respondents. Data were analyzed by paired sample t-test with a significance level of 95%. Based on the results of the study note that the t-value for knowledge of citrus farmers is 6,335 with p sig. 0,000